Our children too : a history of the Black Caucus of the Society for Research in Child Development, 1973-1997, in celebration of the first 25 years - Slaughter Kotzin, Diana; Garrett, Aline M.; Harrison-Hale, Algea O. (Boston, Mass. : Blackwell, 2006)
Key thematic issues include: cultural deficit versus cultural difference; linkages between poverty, race, and empowerment; advocacy versus objectivity in scientific research; and how the cultural or racial identity of the researcher informs scientific knowledge. The collaborations of Caucus members and others in SRCD modified the lens through which children of racially and ethnically diverse backgrounds are portrayed in the scientific literature.--cf. back cover.
Introduction -- Abstract -- Section I: Focus on Caucus history -- Section II: Teaching and mentoring.
Includes bibliographical references.
Keywords: Society for Research in Child Development. -- Black Caucus; African American children; Child development